Clinical features and treatment outcomes of septic arthritis due to Mycobacterium massiliense associated with intra-articular injection: a case report. (December 2016) - Lee, Haekyung; Hwang, Dohui; Jeon, Minchul; Lee, Eunjung; Kim, Taehyong; Yu, Shi; Kim, Yongbeom; Lee, Byung-ill
Abstract Background There are increasing reports on nosocomialMycobacterium massiliense infection, but septic arthritis and osteomyelitis because of that microorganism is rare. This report focuses on the clinical aspects ofM. massiliense arthritis outbreak concurrent with soft tissue infection. Case presentation An outbreak of septic arthritis among patients who had been injected at a single clinic occurred in South Korea between April and September 2012. This may be associated with repeated injection of triamcinolone contaminated withM. massiliense. Nine of the Korean patients visited our hospital complaining of painful swelling of the knees. During treatment course, patients are suffered from soft tissue abscess around the injection site. Acid-fast bacilli culture for infected tissue was positive in five patients, and polymerase chain reaction for non-tuberculous mycobacteria was positive in four patients. They were treated with antibiotics, repeated arthroscopic surgeries, incision and drainage for a long time. All patients were eventually cured but three patients have suffered from a decreased range of motion. Conclusion Early clinical suspicion and microbiological diagnosis are key factors in reducing morbidity since septic arthritis withM. massiliense manifests late after the injection and treatment of it is a laborious process.